Minimization of inorganic particulate matter emissions with a novel multi-fuel combustion technology that enhances inorganic retention in a compact updraft fixed-bed. (15th June 2022) - Archan, Georg Albert Rupert; Scharler, Robert; Buchmayr, Markus; Kienzl, Norbert; Hochenauer, Christoph; Gruber, Johann; Anca-Couce, Andrés
Highlights: Fuel-flexible biomass combustion technology with low emissions developed. Compact updraft fixed bed served as an efficient filter for inorganic particles. Temperature and minor element distribution measured across fixed bed height. Different potassium retention mechanisms identified for woody and herbaceous fuels. Conflicting literature on potassium release in fixed beds for wood clarified. Abstract: A novel biomass combustion technology was investigated that operates at a low oxygen content under fixed-bed and double air staging conditions. This technology was used to achieve extremely low NOX and particle matter emissions in a 30 kW lab-scale reactor, displaying high fuel flexibility and no slagging. In this experimental work, the aim was to minimize inorganic particulate matter emissions, this aim was achieved by enabling the very low release of inorganics such as K from the fixed bed, which operates like a compact updraft gasifier. The elemental composition of the employed fuels, emitted dust particles, and fuel particle samples taken at three different heights within the fixed bed, and the bed temperatures were measured. The main objective in this study was to determine and understand the different processes of inorganic matter release that take place within the compact fixed bed. The results show that 98% and 99.7% of the K could be retained in the fixed bed for wood chips and miscanthus pellets, respectively, thus minimizing the particulate matter emissions. Different processes in the context of K release within the fixed bed could be identified for silica rich/agricultural and calcium rich / woody fuels, respectively and inconsistencies in the literature on these mechanisms could be resolved. In the case of miscanthus pellets, K is retained in silicates, and no accumulation of K, Cl and S occurs in the fixed bed above. In the case of wood chips, on the other hand, there is an unexpected K accumulation in the fixed bed, which is due to the release of K in the hot oxidation zone and the subsequent formation of large amounts of K chlorides and sulfates by condensation in the cooler upper region. Furthermore, for woody fuels, bounding or intercalation of K into the char matrix plays a more important role than the formation of carbonates in avoiding K release from the bed.